Threshold Levels of Environmental Quality and Fiscal Decentralization on Economic Growth in Indonesia before, during and after COVID-19 Pandemic - Malik Cahyadin; Mehilda Rosdaliva; Selfia Bintaringintyas; Yunastiti Puwaningsih; Yong Sze Wei (Universitas Negeri Malang, 2024)
Environmental quality can stimulate a certain level of economic growth. Besides, the fiscal decentralization will enhance economic growth by improving a better condition for a local government budget. In the COVID-19 pandemic, the government should work hard to address a higher level of economic growth. Therefore, the threshold levels of environmental quality and fiscal decentralization can be assessed to maintain economic growth in the long-run. This study estimates the threshold levels of environmental quality and fiscal decentralization on economic growth for 34 provinces in Indonesia before, during and after COVID-19 pandemic. The cross-section threshold regression was employed. The findings reveal that before COVID-19 pandemic the threshold levels of fiscal decentralization and environmental quality were 15.18% and 74.97, respectively. During COVID-19 pandemic these levels were 15.32-27.33% and 74.71-74.97, respectively. Meanwhile, after COVID-19 pandemic these levels were 11.99% and 77.69, respectively. Therefore, the local policymakers should manage the local fiscal policy under prudent and sustainable patterns to enhance the local economic growth. They should also pay more attention to qualify the certain level of environmental quality to guarantee the local green growth.